Social control system and autocratic regime stability in North Korea - Kim, Jung-eun (2022)
How do autocratic regimes maintain stability and why are some more durable than others? This study argues that the concept of social control adds value in explaining durable autocracies and attempts to connect the scholarship on social control with autocracy research. To that end, this study develops a theoretical framework of social control system, which combines ideological, physical, and daily life control. These control mechanisms can be implemented reactively or proactively and, depending on the circumstances, they either work alone or simultaneously to maximize the effect of control. To test the theory of the social control system, this dissertation conducts an in-depth case study on North Korea. It uses North Korean publications and declassified documents on North Korea from its former communist allies as primary sources as well as secondary literature to provide background information and apply theoretical explanation. North Korea is a highly repressive and long-lasting dictatorship that has undergone three-generational hereditary succession despite various hardships. I examine three critical episodes when the stability of the North Korean regime was severely challenged. These three cases are examined chronologically and the chosen temporal periods match the periods of the three leaders of North Korea – from the founder Kim Il Sung to Kim Jong Il and the incumbent leader Kim Jong Un. I argue that the North Korean regime survived political shocks and maintained stability due to its social control system and its adaptation to the changing circumstances.